2003
DOI: 10.1097/01.lab.0000054178.01162.e4
|View full text |Cite
|
Sign up to set email alerts
|

The Myofibroblastic Conversion of Peribiliary Fibrogenic Cells Distinct from Hepatic Stellate Cells Is Stimulated by Platelet-Derived Growth Factor During Liver Fibrogenesis

Abstract: SUMMARY:The origin of myofibroblasts and the factors promoting their differentiation during liver fibrogenesis remain uncertain. During biliary-type fibrogenesis, the proliferation and chemoattraction of hepatic stellate cells (HSC) toward bile ducts is mediated by platelet-derived growth factor (PDGF), while myofibroblastic conversion of peribiliary cells distinct from HSC also occurs. We herein examined the phenotype of these peribiliary myofibroblasts as compared with myofibroblastic HSC and tested whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
187
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 211 publications
(201 citation statements)
references
References 39 publications
12
187
2
Order By: Relevance
“…Although activated HSC are undoubtedly the major producers of the excessive and abnormal ECM in liver fibrosis, these cells are heterogeneous in vivo, and may derive from different precursors, including portal or perivenular fibroblasts, 20 circulating fibrocytes, 7,21 or from epithelial-mesenchymal transition (EMT) 9,10 (Fig. 1).…”
Section: In Vitro Modelsmentioning
confidence: 99%
“…Although activated HSC are undoubtedly the major producers of the excessive and abnormal ECM in liver fibrosis, these cells are heterogeneous in vivo, and may derive from different precursors, including portal or perivenular fibroblasts, 20 circulating fibrocytes, 7,21 or from epithelial-mesenchymal transition (EMT) 9,10 (Fig. 1).…”
Section: In Vitro Modelsmentioning
confidence: 99%
“…Data were collected, analyzed with Sequence Detector v1.7 software (Applied Biosystems) and expressed as a copy number reported to the amount of 18S RNA or as a relative amount (2 Ϫ⌬⌬CT ), as reported. 22 Immunohistochemistry. BSEP immunolabeling was performed on liver tissue cryosections using an anti-BSEP polyclonal antibody, and a three-step immunoperoxidase method, as reported.…”
Section: Methodsmentioning
confidence: 99%
“…PDGF is the most potent proliferating stimulus for HSCs (4,8). It has been reported that the PDGF receptor (PDGFR) is up-regulated along with HSC activation in carbon tetrachloride (CCl4)-and bile duct ligation-induced liver injuries (9)(10)(11). Dominant-negative soluble PDGFR or anti-sense PDGF gene transfer significantly attenuated experimental liver fibrosis development (12,13).…”
Section: Introductionmentioning
confidence: 99%